Assessing green home performance: The case study from a developing country - Tan, Teck-Hong * (2013)
This paper reviews data from a survey to determine the satisfaction level of homeowners towards their residence in terms of green features in Iskandar Malaysia. In this survey, 295 copies of questionnaire forms were being distributed to green home owners and 116 forms were returned. Results show that homeowners are most satisfied with the green features of high ceiling, north-south orientation, double-glazed panel glass doors and windows, solar panel system and landscaped parks with facilities. Rain water harvesting system and low-flow water fixtures, on the other hand, are the least satisfied green features among homeowners. Greater knowledge of green home attributes that influence housing satisfaction could lead to better understanding and prediction of decision making in determining homeowners’ needs.